Determination of dimetridazole and metronidazole in poultry and porcine tissues by gas chromatography–electron capture negative ionization mass spectrometry - Ho, Clare; Sin, Della W.M.; Wong, K.M.; Tang, Hubert P.O. (Analytica chimica acta, 2005)
A sensitive and selective method using gas chromatography–electron capture negative ionization mass spectrometry (GC–ECNI-MS) for analysis of dimetridazole (DMZ) and metronidazole (MNZ) in poultry muscles, porcine kidney and liver, and chicken liver, was developed and validated for the purpose of food surveillance testing of the residues of these two nitroimidazoles in various types of animal tissues in the Hong Kong Special Administrative Region. Before homogenization and extraction with toluene, [2H 3]dimetridazole-(DMZ-d 3) and secnidazole (SNZ) were added to tissue samples as internal standards. The organic extracts were mixed with n-hexane and subject to solid-phase extraction cleanup by amine extraction columns. MNZ and SNZ were derivatized with BSA prior to GC–ECNI-MS determination. Good recovery and precision were obtained and the limit of detection was below parts per billion levels for poultry and porcine tissues. The method could also be applied for the detection of the hydroxylated metabolite of DMZ.